Typical Kawasaki Disease in a Pediatric Patient with Pre-existing Atopic Disorder - Thomas, Rimisha; Varghese, Arshamol; Alosious, Aaja; George, Tany Maritta; Vilapurathu, Jobin Kunjumon (Journal of Pharmacy Practice and Community Medicine)
Kawasaki disease (KD), is an acute febrile illness that is known to be a leading cause of cardiovascular morbidity, if not adequately treated. The association between preexisting allergic diseases and Kawasaki disease has been the subject of mounting clinical interest. We herein report a case of typical Kawasaki syndrome in a seven-year-old child with preexisting atopic disorder. Once the diagnosis of Kawasaki was established, intravenous immunoglobulin and oral aspirin were initiated at a dose of 2 g/kg body weight and 100 mg/kg/day respectively. Response to treatment was remarkable and the he was discharged on the fifth day post admission with aspirin to be continued at maintenance dose. This report highlights the importance of prompt diagnosis and management of Kawasaki and the need for future investigations on the risk of this condition in children with history of immune disequilibrium.
Keywords: Kawasaki disease; Atopic disorder; Vasculitis; Immunoglobulin